Research on the Impact of Smart City Construction on High-quality Economic Development - Song, Shibo (International Journal of Social Sciences and Public Administration, 2025)
The construction of smart cities has been positioned by many local governments as an engine to complete industrial structure upgrading and lead high-quality regional economic development. This article selects data samples from 261 prefecture-level cities in China from 2004 to 2021 and uses a quasi-natural experiment method to conduct an in-depth study on the relationship between smart city construction and high-quality urban economic development. The results show that the construction of smart cities mainly realizes the spillover effect of high-quality urban economic development by enhancing the resilience level of cities. This spillover effect is relatively significant in China's eastern and central regions and is more pronounced in cities with larger population scales. Therefore, it is of great significance to reasonably expand the pilot scope of smart cities and formulate appropriate urban smart network system plans according to the characteristics of different regions to enhance urban resilience, prevent systemic risks, and thus promote high-quality urban economic development.